Chest pain: if it hurts a lot, is heart attack more likely?. (April 2016) - Body, Richard; Lewis, Philip S.; Carley, Simon; Burrows, Gillian; Haves, Bethany; Cook, Gary
Abstract : Background: In previous studies including patients with suspected cardiac chest pain, those who had acute myocardial infarction (AMI) reported more severe chest pain than those without AMI. However, many patients with AMI present with very mild pain or discomfort. We aimed to investigate whether peak pain severity, as reported by patients in the Emergency Department, has any potential role in the risk stratification of patients with suspected cardiac chest pain. Methods: In this secondary analysis from a prospective diagnostic cohort study, we included patients presenting to the Emergency Department with suspected cardiac chest pain. Patients were asked to report their maximum pain severity using a 11-point numeric rating scale at the time of initial presentation. The primary outcome was a diagnosis of AMI, adjudicated by two independent investigators on the basis of reference standard (12 h) troponin testing. Results: Of the 455 patients included in this analysis, 79 (17.4%) had AMI. Patients with AMI had marginally higher pain scores (eight, interquartile range 5–8) than those without AMI (seven, interquartile range 6–8, P =0.03). However, the area under the receiver operating characteristic curve for the numeric rating scale pain score was 0.58 (95% confidence interval 0.51–0.65), indicating poor overall diagnostic accuracy. AMI occurred in 12.1% of patients with pain score 0–3, 17.1% with pain score 4–6 and 18.8% with pain score 7–10. Among patients with AMI, pain score was not correlated with 12-h troponin levels ( r =−0.001, P =0.99). Conclusion: Pain score has limited diagnostic value for AMI. Scores should guide analgesia but shift the probability of AMI very little, and should not guide other clinical management.